2018
DOI: 10.1016/j.eurpsy.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Affectively salient signal to random noise might be used to identify psychosis vulnerability in severe mental disorders

Abstract: Experimental paradigms indexing the tendency to detect affectively salient signals in noise may be used to identify liability to psychosis in people with vulnerability. Its predictable value in other diagnostic categories and general population requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…22 White Noise Task. The WNT was used to assess the incidence of SIs heard in white noise 9,11,27,28 (figure 1). Participants, wearing earphones, sat in a room with a trained experimenter and were presented with either: (1) white noise only, (2) white noise plus clearly audible neutral speech, and (3) white noise plus barely audible neutral speech.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 White Noise Task. The WNT was used to assess the incidence of SIs heard in white noise 9,11,27,28 (figure 1). Participants, wearing earphones, sat in a room with a trained experimenter and were presented with either: (1) white noise only, (2) white noise plus clearly audible neutral speech, and (3) white noise plus barely audible neutral speech.…”
Section: Instrumentsmentioning
confidence: 99%
“…SI scores were skewed, as expected, because participants expressed a low rate of false alarms. To address this, following previous work, 9,27,28 performance was parameterized as 3 dichotomous variables according to responses during the white noise-only condition: Each participant was rated as 1 or 0 depending on whether they heard at least 2 SIs that they perceived as (1) neutral, (2) positive or negative, or (3) unsure whether they were neutral, positive, or negative. We included a threshold of at least 2 SIs per condition, to exclude possible erroneous attributions of SIs.…”
Section: Groups For Analysis Comparisons Were Made Between the Entire...mentioning
confidence: 99%
See 1 more Smart Citation
“…El ruido blanco se ha convertido recientemente en un paradigma experimental para propiciar y evaluar ilusiones del habla que pudieran suponer una indicación de vulnerabilidad a la psicosis (Catalan et al, 2018;Galdós et al, 2011;Schepers et al, 2019). La tarea experimental consiste en presentar a través de auriculares un sonido monótono grabado a fin de ver si los sujetos reconocen patrones verbales o ilusiones del habla.…”
Section: El "Sumador Verbal" Ruido Blanco Para La Psiquiatríaunclassified
“…Similarly, in the case–sibling–healthy participant study by Galdos and colleagues, stronger associations were apparent with affective speech illusions (15). It has been suggested that affective salience might characterize speech illusions in individuals at risk for clinical outcomes (20, 21) and may be mediated in part by cognitive alterations (22), although another study did not find evidence for this (15). Therefore, further research is required to evaluate differences in psychopathology, cognition, and affective valence of speech illusions in patients, siblings, and healthy participants.…”
Section: Introductionmentioning
confidence: 99%